Antimicrobial spectrum and Phytochemical study of Hopea parviflora Beddome Saw dust extracts - K.V. Chethan Kumar, Sukesh, K.R. Chandrashekar, Shilpa Bhat, Sonia Mercy Lobo (Journal of Phytology, 2009)
The present study evaluates the antimicrobial and phytochemical activity of Hopea parviflora Beddome an endemic tree belonging to Dipterocarpaceace against certain bacteria (Escherichia coli, Proteus vulgaris, Pseudomonas aueroginosa, Klebsiella puemoniae and Staphylococcus areus). The aqueous, methanol and ethanol extracts were found to be most effective against Staphylococcus areus. Ethanol extracts compared to other extracts was highly effective against most of the test organisms except Escherichia coli. TLC seperation of ethanolic extracts yielded 4 fractions with retention factor (Rf) of 0.58, 0.60, 0.77 and 0.99. Fraction with Rf value of 0.99 was shown to contain antibacterial activity.